"Soldiers of the faith": a comparative analysis of White Power songs and Islamic State nasheeds - Pieri, Zacharias (Deviant behavior, 2023)
The nonviolent activities of extremists have the capacity to shed important light on how such groups think and frame the world around them. This paper provides a comparative insight into the framing activities of Islamic State and white power (WP) groups through an analysis of the song lyrics that have emerged from these scenes. In doing so, we seek to understand the role that culture, particularly music, plays in constructing the worldview of both white supremacists and jihadists. Through analyzing song lyrics we explain how those writing and performing the music can shape the contexts in which participants operate. What emerges is that despite differences in the stated belief systems of Islamic State and white supremacists, the ways in which the underlying worldview is constructed is similar. Both focus on highlighting grievances and see their own in-group as facing real and prominent threats, often due to liberal values. Both see Jewish people as a corrupting force in the world, and both have a clear direction on overcoming such threats with direct calls to action. Both groups tap into global narratives against multiculturalism, globalization, and the global international order, which they view as inherently damaging to their own group interests.